Penanaman Sikap Kemandirian dan Berfikir Kreatif pada Usia Remaja melalui Kegiatan Ekstrakurikuler Pencak Silat SMPIT Nurul Azmi - Bachtiar, Muhamad Abdul Rozaq; Muhtar, Tatang; Dinangsit, Dinar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The aim of this research is to determine the effect of practicing pencak silat training patterns on increasing the attitude or character of independence and creative thinking of teenage students in extracurricular pencak silat activities at SMPIT Nurul Azmi and how big the influence of practicing these training patterns is. The research method used is the pre- experimental with a One group pretest-posttest design. At meeting 1, namely carrying out a pretest (initial test), the results were relatively low, so the treatment was given 12 times and ended with carrying out a posttest (final test) to obtain data or results that were expected to increase in the experimental group. The results of the research show that the sig value, (2-tailed) 0.000 < 0.05, which means that Hı is accepted and H₀ is rejected, so from this research there is an influence of pencak silat training patterns on increasing students' independent attitudes and creative thinking. After that, to find out the magnitude of the influence, the researchers used a regression test and the results obtained were that the influence of pencak silat extracurricular activities by providing this training pattern was 33.3% on the aspect of independence, and 54.3% on the aspect of creative thinking. The conclusion of this research is that extracurricular Pencak Silat can increase independence and creative thinking in adolescents. Keywords: Creative Thinking, Extracurricular, Independence, Pencak Silat